Book review: de Waal, Alex. 2018: Mass Starvation: The History and Future of Famine. (July 2019) - Cochrane, Logan
De Waal, Alex. 2018: Mass Starvation: The History and Future of Famine. Cambridge: Polity Press. 264 pp. 24.95. ISBN: 9781509524679.